Oxidation of Aliphatic Alcohols by Potassium Iodate: A Kinetic Approach - Patel , Aman.; Tiwari, Anjali; Sindhav, Bhakti. (Journal of Neonatal Surgery, 2025)
The present study investigates the oxidation kinetics, mechanistic pathway, and thermodynamic behaviour of four alcohols—n‑butanol, octanol, isopropyl alcohol, and 2‑chloroethanol—oxidized by potassium iodate (KIO₃) in an acidic medium. Reaction progress was monitored via iodometric titration, and kinetic analysis revealed a first-order dependence on alcohol concentration and an inverse dependence on [KIO₃] for all substrates. The proposed mechanism involves the formation of reactive iodine species such as halic acid (HIO₃) and hypoiodite ion (IO⁻). The rate of oxidation was found to be influenced by alcohol structure, particularly the presence of electron-withdrawing groups, chain length, and branching. Among the alcohols studied, 2‑chloroethanol exhibited the highest oxidation rate, attributed to inductive activation by the chlorine substituent. n‑Butanol followed due to its unbranched primary structure, while isopropyl alcohol showed moderate reactivity as a secondary alcohol. Octanol demonstrated the lowest rate, likely due to steric hindrance and reduced solubility in the aqueous medium. Activation energies (Ea) and related thermodynamic parameters were determined using the Arrhenius equation, supporting the structure–reactivity trends observed. The overall oxidation rate sequence was: 2‑chloroethanol > n‑butanol > isopropyl alcohol > octanol. These findings highlight the role of molecular structure in modulating oxidation rates, offering practical insights for designing greener oxidation systems for industrial alcohols.